Soberania alimentar: dimensões material, prático-política, utópica e contraposição à [des]ordem do Sistema Agroalimentar - Costa, Joaquim Gonçalves da (2018)
This thesis analyzes Food Sovereignty under the perspective, historical-material content [projection] built from the praxis of the workers organized in Popular Movements, and Social Organizations, members of Via Campesina, the progenitor of the concept presented in 1996 to society. The concept of Food Sovereignty is taken in its totality and multidimensionality [material basis: territorial, food, genetic, energy and water; and social basis: economic, political, cultural, environmental and social] as an alternative historicalpolitical project of organizing 'food systems' and provision of food, contraposition to the [dis] order of the Agrifood System. It is demonstrated that the materialization of Food Sovereignty in its prescribed radicalism and as a historical development, considering its multiple basic and social dimensions, is imbricated with the material, practical-political and utopian dimensions, and therefore, presupposes the necessary practical mediations Agrarian Reform [Popular], the Public Policy, Agro ecology and Human Formation for this transition process. The analysis also dedicates attention on issues related to hunger and food nutritional insecurity and how society has sought and is seeking to address these problems. Based on this, the historical genesis of the concepts of Food and Nutrition Security and Food Sovereignty, and what underlies this debate, concludes that the Food and Nutrition Security policies integrate and compact with the systemic order, while the initiatives and the projection of Food Sovereignty are inscribed in the order of rupture, mediation and overcoming order, and in the construction of another hegemony. Also relevant are the analysis of the Brazilian experience both in the issue of social participation, in the debates and demands for public policies, and in the actions, programs and policies of Food and Nutrition Security implemented. From this, the broad lines for the implementation of policies with material force inducing transformation from the perspective of Food Sovereignty are perceived, which focused on the conclusion of the confirmation of the hypothesis that the policies implemented do not guarantee Food and Nutrition Security and are distant from the values and principles advocated by Food Sovereignty, and are mostly colliding. Finally, the horizon composed by the radicalism of the concept in its process of ideation and its utopian dimension [with the germs of the new] is that they shed light and determine the substance of practical mediations under construction.